2011
DOI: 10.1080/10454438.2011.581586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Animal Proteins in Practical Diets on Growth and Economic Performance of Climbing Perch,Anabas testudineus(Bloch)

Abstract: A ten-week feeding trial was carried out to evaluate animal proteins, either alone or in combination (1:1:1), on the growth performances and economic benefit of climbing perch, Anabas testudineus. Four iso-proteinous (40%) diets were prepared, using fishmeal, protein concentrate, and meat and bone meal as major protein source in diets 1, 2 and 3, respectively, while diet 4 consisted of an equal proportion (1:1:1) of the above protein sources. Triplicate groups of fish (0.53 ± 0.02 g) were randomly stocked in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The lowest final weight, weight gain (%), SGR, FCR, and PER were found in fish fed diets containing only MBM as a protein source. Similar results have also been observed with climbing perch where significantly lower growth and feed utilization were found in fish fed MBM as major protein (Kader et al 2009). The amino acid analysis showed that all the EAAs of MBM were lower compared to those in PC (Table 1), which is also reflected in the experimental diets (Table 2).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The lowest final weight, weight gain (%), SGR, FCR, and PER were found in fish fed diets containing only MBM as a protein source. Similar results have also been observed with climbing perch where significantly lower growth and feed utilization were found in fish fed MBM as major protein (Kader et al 2009). The amino acid analysis showed that all the EAAs of MBM were lower compared to those in PC (Table 1), which is also reflected in the experimental diets (Table 2).…”
Section: Discussionsupporting
confidence: 85%
“…Diets are also often developed without any scientific or nutritional consideration of the species in question. In a recent study, no significant difference was observed in the performances of climbing perch, Anabas testudineus , by feeding locally available FM or commercially imported PC (Kader et al 2009). Therefore, the present study was undertaken to evaluate MBM as replacement for PC in the practical diet of sutchi catfish in pond conditions.…”
mentioning
confidence: 98%
“…() and Kader, Bulbul, Ahmed et al . () respectively. Crystalline AAs and/or other ingredients supplementation could reduce the AA imbalance and improve the EAA composition pattern of the diet, and subsequently might improve the growth of climbing perch, which needs to be conducted in further study.…”
Section: Discussionmentioning
confidence: 96%
“…In Bangladesh, different alternative protein sources are used in aquafeeds without any scientific and nutritional consideration of the species in question. Kader, Bulbul, Ahmed, Hossain, Hossain and Koshio () evaluated the potential of MBM and PC in the diets of climbing perch. In another study, Hossain, Basak, Kibria and Kohinoor () found that 75% fishmeal protein can be replaced with PC and MBM mixture.…”
Section: Introductionmentioning
confidence: 99%